2022
DOI: 10.5187/ait.2022.9.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental β-mannanase on in vitro disappearance of dry matter in feed ingredients for swine

Abstract: The present study was aimed to investigate the effects of supplemental β-mannanase on in vitro ileal disappearance (IVID) and in vitro total tract disappearance (IVTTD) of dry matter (DM) in barley, canola meal, copra meal, corn, corn distillers dried grains with solubles, cottonseed meal, palm kernel meal, soybean meal, and wheat for pigs. Feed ingredient samples were finely ground and divided into the control group and the treatment group. The samples of the control group were prepared to contain 990 g/kg te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(24 reference statements)
2
0
0
Order By: Relevance
“…The IVID of DM and CP in CSBM based on the conventional in vitro procedure observed in the present study was comparable to those reported in previous studies [12,32]. In the present study, thermo-mechanical processing improved the IVID of CP of SBM in the conventional in vitro procedure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The IVID of DM and CP in CSBM based on the conventional in vitro procedure observed in the present study was comparable to those reported in previous studies [12,32]. In the present study, thermo-mechanical processing improved the IVID of CP of SBM in the conventional in vitro procedure.…”
Section: Discussionsupporting
confidence: 90%
“…The value of the IVTTD of DM in CSBM observed in the present study is similar to those reported in previous studies [10,32]. The greater IVTTD of DM in TSBM compared with CSBM can be partially explained by the greater IVID of DM and IVID of CP in TSBM, indicating that thermo-mechanical processing may have made proteins more digestible in the upper gut of pigs.…”
Section: Discussionsupporting
confidence: 90%